The determine of possible drug interaction of clarithromycin - Ceylan, Cengizhan; Karataş Koçberber, Emine; Taner, Neda; Berk, Barkın (Springer, 2016)
Phenytoin is an antiepileptic drug which is eliminated by CYP2C9, CYP2C19 (less important: CYP2C18, CYP3A4) enzyme. Therapeutic concentration range is very important due to the narrow therapeutic drug levels. Targeted therapeutic concentration range is 10–20 mg/L (40–80 lmol/L) in blood serum for adults and children older than 3 months. Phenytoin has highly variable pharmacokinetics due to its complex of binding to Albumin (%90). It is dif?cult to determine the correct dosage of this drug because of signi?cant dose related toxicity. It is also important for inpatient in intensive care unit.
WOS: 000384561800054
Keywords: Pharmacology; Pharmacy; Clinical Pharmacy